Our Little Garden - Toiskallio, Sointu (Journal of Anthropological Films, 2025)
Our Little Garden explores in the hustle of Santiago de Chile's megacity how gardeners of different ages have found a respite, a connection to the soil and a community in an organic urban garden at the edges of the capital city. Organic gardening not only produces agrochemical-free food but also a space where different species help each other to live. 19-year-old Alonso dreams of one day being self-sufficient. 76-year-old Ana María likes to keep her mind active by learning and enjoying plants with all her senses. Heriberto has recovered from cancer and wants to cleanse his body inside and out. Dipping one’s hands into the soil not only prompts the beginning of a plant's life but is also a therapeutic experience. Here, a small piece of land offers gardeners an opportunity to practice traditional permaculture and return to a time when people were more attuned to the rhythms of plants and other organisms. This collaborative film project was accompanied by a Master’s thesis analyzing how health and well-being are experienced and conceptualised in relationships built around connections with nature, and how using collaborative videography can increase phenomenological sensory knowledge through involvements with research participants during ethnographic fieldwork.